Early clinical indicators of acute kidney injury caused by administering high-dose methotrexate therapy to juvenile pigs - Buddington, Randal K.; Wong, Thomas; Buddington, Karyl K.; Mikkelsen, Torben S.; Cao, Xueyuan; Howard, Scott C. (Frontiers in Nephrology, 2023)
Early identification of compromised renal clearance caused by high-dose methotrexate (HDMTX) is essential for initiating timely interventions that can reduce acute kidney injury and MTX induced systemic toxicity. We induced acute kidney injury (AKI) by infusing 42 juvenile pigs with 4 g/kg (80 g/m2) of MTX over 4 hours without high volume alkalinizing hydration therapy. Serum creatinine and MTX were measured at 15 time points up to 148 hours with 10 samples collected during the first 24 hours after the start of the HDMTX infusion. During the first 28 hours 81% had increases of serum creatinine in one or more samples indicative of AKI (>0.3 mg/dL increase). A rate of plasma MTX clearance less than 90% during the initial 4 hours after the HDMTX infusion and the sum of serum creatinine increases at 6 and 8 hours after starting the infusion greater than 0.3 mg/dL were predictive of AKI at 28 hours (P’s <0.05 and <0.001). At conclusion of the infusion, pigs with creatinine more than 0.3 mg/dL higher than baseline or serum MTX greater than 5,000 µmol/L had an increased risk of severe AKI. Our findings suggest serum samples collected at conclusion and shortly after HDMTX infusion can be used to predict impending AKI. The pig model can be used to identify biological, environmental, and iatrogenic risk factors for HDMTX induced AKI and to evaluate interventions to preserve renal functions, minimize acute kidney injury, and reduce systemic toxicity.